Learning Innovation and Assistive Technology for Students with Special Needs in Higher Education - Muhammad Jailani; Chandra Anugrah Putra; Agung Riadin; Muhammad Andi Setiawan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Communication technology has been very developed in Indonesia. Everything can be accessed and enjoyed easily. Someone in Sabang can easily communicate with someone in Merauke because of the sophistication of today’s technology. Persons with disabilities also have the same rights and obligations as other human beings. However, they often have limitations to make many humans seem to alienate them. Even though they also have the right to get a good education and quality learning. Currently, people with disabilities worldwide reach 1 billion people or 12% of the world’s population, and 80% are in developing countries. According to the Indonesian Ministry of Social Affairs records, in 2011, the number of people with disabilities in Indonesia reached 7 million people, or about 3% of the total population in Indonesia, which amounted to 238 million. According to Law No. 4 of 1997 concerning persons with disabilities, persons with disabilities are defined as any person who has physical and mental disorders, which can interfere or become obstacles and obstacles for him to perform properly, consisting of persons with physical disabilities, persons with mental disabilities. , people with physical and mental disabilities